PEMBERLAKUAN INPRES NO. 1 TAHUN 2022 TENTANG OPTIMALISASI PELAKSANAAN PROGRAM JAMINAN KESEHATAN NASIONAL DALAM RANGKA MENYEHATKAN BPJS KESEHATAN - Syaid, Aqris (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
One of the most striking problems that BPJS Kesehatan has experienced for almost 8 (eight) years of managing the National Health Insurance is the existence of a deficit in the BPJS Health Social Security Fund. Even though in 2021 there has been a surplus of the Social Security Fund for Health, the potential for a deficit to occur again in 2023. In order to overcome the potential threat of a deficit in the Social Security Fund for Health BPJS or in order to make the Social Security Fund always healthy (surplus) BPJS Health, the Government makes and enforces Presidential Instruction Number 1 of 2022 concerning Optimization of the Implementation of the National Health Insurance Program which basically requires every Indonesian citizen to become a National Health Insurance Participant of BPJS Health in active status as a requirement to get 8 (eight) ) public service. The Presidential Instruction is used by the Government as a means or tool in an effort to achieve the desired ultimate goal, namely so that there will be no more deficits in the Social Security Fund for Health BPJS, thereby no longer burdening the APBN. Whereas the drafting and enactment of Presidential Instruction Number 1 of 2022 concerning Optimizing the Implementation of the National Health Insurance Program still does not fulfill the law aspired to by the Indonesian constitution, namely a law that provides a sense of justice, certainty and prosperity. This writing aims to explain and find out about the enactment of Presidential Instruction Number 1 of 2022 concerning Optimization of the Implementation of the National Health Insurance Program as a legal norm that is currently in effect (ius contitutum) through studies, studies and analysis of research methods so that it can be known regarding the accuracy of the choice of application of norms the law in the legal perspective aspired to by the State Constitution, namely law that has justice, certainty and welfare (ius constituendum).